1962
DOI: 10.1152/jappl.1962.17.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Use of respiratory quotients in assessment of aerobic work capacity

Abstract: Oxygen uptake and carbon dioxide output were measured in 32 untrained subjects during exercise on the bicycle ergometer. It was shown that the work respiratory quotient (RQ) under standardized conditions can be used as a measure of physical fitness. ΔRQ (work RQ minus 0.75) increases logarithmically with the work load and maximal O2 uptake is reached at a ΔRQ value of 0.40. This observation offered the possibility of predicting the maximal O2 uptake of a person, based on the measurement of RQ during a single b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
3

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(60 citation statements)
references
References 0 publications
3
53
1
3
Order By: Relevance
“…Expired gas data was used to define V O 2max (greatest 30 s mean value) and the relevant sub-maximal running speeds for the experimental trials. All subjects were deemed to have attained V O 2max , as they achieved ≥2 of the following criteria: a plateau in V O 2 in the final exercise stage (Taylor et al 1955), RER ≥1.15 (Issekutz et al 1962), HR within 10 b min −1 of age-predicted maximum (220-age), RPE ≥19, blood [lactate] ≥8 mM (Midgley et al 2007). …”
Section: Maximal Exercise Testingmentioning
confidence: 99%
“…Expired gas data was used to define V O 2max (greatest 30 s mean value) and the relevant sub-maximal running speeds for the experimental trials. All subjects were deemed to have attained V O 2max , as they achieved ≥2 of the following criteria: a plateau in V O 2 in the final exercise stage (Taylor et al 1955), RER ≥1.15 (Issekutz et al 1962), HR within 10 b min −1 of age-predicted maximum (220-age), RPE ≥19, blood [lactate] ≥8 mM (Midgley et al 2007). …”
Section: Maximal Exercise Testingmentioning
confidence: 99%
“…Although the maximal respiratory exchange ratio varies significantly between individuals, a value Ͼ1.1 has been suggested as subsidiary evidence that a true V O 2 max has been attained. 35 The commonly used Weber classification of exercise capacity in heart failure patients is provided in Table 1. 36 A derivation of the Weber classification has also been applied to the level of VT and to the increase in CO with activity.…”
Section: Heart Failurementioning
confidence: 99%
“…V O 2max was defined as the greatest 15-s mean value obtained. Our criteria for reaching V O 2max required a plateau in oxygen consumption (i. e., an increase in treadmill grade with no increase in oxygen consumption) and/or a respiratory exchange ratio (RER) over 1.15 [15]. All of our subjects reached V O 2max criteria.…”
Section: Methodsmentioning
confidence: 88%
“…We increased treadmill speed by 0.45 m · s − 1 (1 MPH) in each subsequent stage during both days. During the final minute of each 4-min stage, we asked subjects to provide a rating of perceived exertion (RPE) on the Borg (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) scale [9], until they reached an RPE of 15 (speed at RPE of 15 = sRPE15) on both days. Previous data have demonstrated that an RPE value of 16 represents an intensity that corresponds closely to LT [22].…”
Section: Methodsmentioning
confidence: 99%